Interaction, communication and engagement in hybrid virtual and augmented reality environments - Li, Yue (2020)
This thesis presents research at the intersection of Extended Reality (XR) and Cultural Heritage - Virtual Heritage (VH). Prior research in VH has used Virtual Reality (VR) for immersive visualisation and Augmented Reality (AR) has been used for enhancing exhibitions. These reality technologies were primarily configured for use within museums, which are limited in terms of physical touch and handling capabilities and remote accessibility. Recent advances in XR and its rapid growth and affordability across various consumer devices are providing new opportunities for cultural heritage to be accessed outside the walls of the museums. However, virtual exhibitions and physical visits are different in many ways. Challenges remain for XR in its ability to emulate physicality and materiality, and the social environments within which interpretation, knowledge and ideas are exchanged. Meanwhile, the diversity of devices that are adopted as a consequence of user preferences necessarily means that technologies developed for users should take into account such a need as audiences are central and core to the activities of cultural institutions. In view of such a need, XR presents many challenges that are unsolved, one aspect of which is related to the concept of Extended Reality itself in its broad spectrum between physical reality and virtual reality. As users adopt their preferred devices within the XR spectrum, it has become essential to investigate the intersection of such use if communication within the spectrum is to be made possible.